Favorable response to third-generation TKI furmonertinib in a patient with early-stage non-small cell lung cancer​ harboring rare compound EGFR mutations: Exon 18 G719C and Exon 20 S768I — A Case Report - Liu, Shihu; Zhang, Jinzi; Dong, Yanfeng; Wang, Yongjie (Frontiers in Oncology, 2026)
EGFR Exon 19 deletions and exon 21 point mutations of EGFR are the most prevalent alterations in lung adenocarcinoma, and patients with these mutations derive substantial clinical benefit from EGFR tyrosine kinase inhibitors (TKIs). Nevertheless, the therapeutic efficacy of TKIs in rare compound EGFR mutations remains unclear. Here, we describe a case of early-stage non-small cell lung cancer (NSCLC) harboring a G719C+S768I compound mutation that achieved complete remission following treatment with furmonertinib. These findings suggest that furmonertinib may represent a promising therapeutic option to improve cure rates in this subset of patients.